Silagem de coproduto de fecularia de mandioca e ureia protegida na dieta de vacas em lactação - Almeida, Kleves Vieira de (2017)
The objective of this study was to evaluate the nutritional and microbiological quality of the cassava starch coproduct silage (CFM) as a function of the silage times 0, 30, 60, 90 and 120 days, the in vitro fermentation kinetics of diets based on CFM dehydrate or silage associated with urea levels, as well as evaluating levels of protected urea associated with cassava starch silage (SCFM) silage in the diet of lactating dairy cows. For the evaluation of the SCFM, a completely randomized experimental design (DIC) with five treatments and four replicates was used. For in vitro fermentation kinetics a DIC was used with five treatments and three replicates. Five cows distributed in a 5x5 Latin square were used for the animal performance. The treatments evaluated were the increasing levels (0%, 0.4%, 0.8%, 1.2% and 1.6%) of protected urea in the concentrate. In the latter, parameters of intake and digestibility of dry matter and nutrients, metabolic parameters, milk production and composition and microbial synthesis were analyzed. For the evaluation of SCFM, bromatological analyzes, in vitro digestibility and microbiological profile were performed. In vitro gas production was measured from the incubation of the diets in flasks equipped with digestion modules. The dry matter content of the SCFM increased linearly. There were no significant differences in organic matter, crude protein, ethereal extract and total carbohydrates. On the other hand, neutral detergent fiber (NDF) increased linearly. There was no effect for digestibility of dry matter and organic matter, however the digestibility of NDF decreased linearly. There was a quadratic effect for the population of lactic acid bacteria. Bacteria of the Clostridium genus have remained constant over time. The main fungi genotypes present in SCFM were Phoma, Cladosporium and Penicillium. For the gas production of diets using urea and dehydrated CFM, there was no effect for fraction A. A linear effect was observed for the fraction C, which comprises lag time, however, the total gas production (A + D) Was not affected. For the diets that used the silage CFM, there was no Fraction A effect, as well as for the lag time, reflecting the same effect observed for the total gas production (A + D). There was no effect on intake of dry matter and nutrients. Milk production was not influenced by the treatments;however some parameters of the composition were affected. The microbial synthesis had no effect on the treatments, with the exception of milk allantoin, which increased linearly. The ensiling of the coproduct of cassava starch was effective up to 120 days due to lowering of moisture and consequent increase in dry matter content. The addition of up to 1.6% of CFM-associated urea in the dehydrated or silage form does not alter gas production in vitro. Taking into account the break-even point, treatment 1.6% was the most profitable in comparison to the others. It is recommended to use the silage from the coproduct of cassava starch and up to 1.6% of protected urea in the concentrate without interfering the dry matter intake and milk production.